2009
DOI: 10.1007/s10534-009-9208-5
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium promoted proliferation and enhanced survival in human cervical carcinoma cells

Abstract: The effect of gadolinium chloride (Gd) on the proliferation of HeLa cells was investigated at lower concentration. The results obtained by MTT and cell cycle analysis showed that Gd promoted proliferation by inducing S phase entry in HeLa cells at the concentration less than 100 microM. It was further evidenced by both an increase in the levels of phosphorylation of retinoblastoma protein (pRb) and a remarkable increase in cyclin E expression. Moreover, the survival of cells, exposed to Gd up to 3-5 days, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Several studies have described qualitatively similar but quantitatively different responses to individual lanthanoids. For example, variation has been reported in regard to protein stabilization in aqueous solution [47], reduction in lacunae formation by osteoclasts [48], and growth modulation in certain mammalian cell lines [14-16]. Other than to note differences among the elements for modulating one cell function or another, there is little that points to a particular chemical property as being critical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have described qualitatively similar but quantitatively different responses to individual lanthanoids. For example, variation has been reported in regard to protein stabilization in aqueous solution [47], reduction in lacunae formation by osteoclasts [48], and growth modulation in certain mammalian cell lines [14-16]. Other than to note differences among the elements for modulating one cell function or another, there is little that points to a particular chemical property as being critical.…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial growth reduction is not universal, however, as increased proliferation and decreased differentiation have also been reported [14, 15]. Lanthanoid-induced growth arrest has also been seen with melanoma cells [16], but the underlying molecular mechanism is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Gadolinium salts are known to inhibit the function of the mononuclear phagocytic system, and have an anticoagulant effect by inhibiting clotting reactions that require calcium (Lee et al 2004;Liao et al 2009). The effects of gadolinium salts on the proliferation and apoptosis of some normal and cancer cells have also been studied extensively (Sato et al 1998;Liu et al 2006;Fu et al 2009;Zhang et al 2009), and these effects related to cell proliferation and apoptosis depend on the concentrations or the types of cells being studied. This suggests that Gd-based treatments have potentials in medical applications in effective therapy of some diseases like cardiac disorders and cancers, and growing interest in the study on the mechanisms of Gd-induced biological effect on cell growth has been aroused.…”
Section: Introductionmentioning
confidence: 99%
“…This method with enhanced mass resolution, mass accuracy, and detection sensitivity, would allow to investigate the role of metabolites and relevant metabolic processes in different states. Previous study has demonstrated that GdCl 3 could inhibit or promote proliferation of several types of cancer cells lines including Hela cells, depending on the concentrations applied (Liu et al 2006;Zhang et al 2009). However, the underlying mechanism involved is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Lanthanides (Ln) have been shown to promote cell proliferation and induce apoptosis depending on Ln species, concentrations and cell types. Most studies have shown that the proapoptosis effect appeared at the concentration higher up to millimolar levels, while proliferative effect often occured at micromolar concentration (Zhang et al 2009). However, recently some lanthanum (III) complexes have been synthesized with diverse ligands including chrysin (Zeng et al 2003), phenanthroline derivatives (Wang et al 2000(Wang et al , 2002Heffeter et al 2006) and coumarin derivatives (Kostova et al , 2006.…”
Section: Introductionmentioning
confidence: 99%